GSK3 suppression upregulates β-catenin and c-Myc to abrogate KRas-dependent tumors. Issue 1 (December 2018) - Kazi, Aslamuzzaman; Xiang, Shengyan; Yang, Hua; Delitto, Daniel; Trevino, José; Jiang, Rays; Ayaz, Muhammad; Lawrence, Harshani R.; Kennedy, Perry; Sebti, Saïd
Abstract Mutant KRas is a significant driver of human oncogenesis and confers resistance to therapy, underscoring the need to develop approaches that disable mutant KRas-driven tumors. Because targeting KRas directly has proven difficult, identifying vulnerabilities specific for mutant KRas tumors is an important alternative approach. Here we show that glycogen synthase kinase 3 (GSK3) is required for the in vitro and in vivo growth and survival of human mutant KRas-dependent tumors but is dispensable for mutant KRas-independent tumors. Further, inhibiting phosphorylation of GSK3 substrates c-Myc on T58 and β-catenin on S33/S37/T41 and their subsequent upregulation contribute to the antitumor activity of GSK3 inhibition. Importantly, GSK3 blockade inhibits the in vivo growth of G12D, G12V, and G12C mutant KRas primary and metastatic patient-derived xenografts from pancreatic cancer patients who progressed on chemo- and radiation therapies. This discovery opens new avenues to target mutant KRas-dependent cancers. Direct targeting of mutant KRas is challenging and alternative approaches are needed. Here they show glycogen synthase kinase 3 (GSK3) to be required for the growth and survival of human mutant KRas-dependent tumors but dispensable for mutant KRas-independent tumors and show GSK3 inhibition to inhibit in vivo growth of Kras mutant patient-derived pancreatic tumors.